Images and strategies of parasocial communication in Belarusian international television programmes - Morozowa, E.I. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2026)
This study examines the phenomenon of one-way, yet emotionally engaging communication within the sphere of international broadcasting on Belarusian Soviet television. The objective of the research is to identify the time- tested images and strategies used to construct such multimodal interaction, referred to as parasocial interaction. The study hypothesizes that the artistic image plays a key role in the communication between the senders and recipients of international television programs. A discursive-historical analysis of polymodal television texts at the interconnected levels of representation, composition, and interaction allowed for the identification of communicative strategies for implementing images of antagonistic reality and the Manichean hero. These strategies include culture-determined modeling and modification of metaphors, idiostyle, and the visual-compositional emphasis on the figure of the sender in the frame. The research identifies the subjective position of the implicitly active recipient, constructed through communicative strategies of dialogized monologue, hypophora, and tracking focus. Furthermore, it defines the generative subjective position of both sender and recipient, implemented through modal paraphrasing formulas, stylistically marked vocabulary, reflective thinking strategies, and legitimation through an external opponent. This study contributes to the scientific field of the communicative history of Soviet Union television. The findings can be utilized by television producers to construct communicative interactivity, thereby determining their competitive advantage in the convergent media market.